PROSES KERJA DAN TATA KELOLA BIROKRASI: MENGINTEGRASIKAN KEGIATAN PIMPINAN DPRD PROVINSI JAWA BARAT KE DALAM MEDIA SOSIAL - Cici Nasirotul Maspufah (Community Empowerment : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
In the context of efficient bureaucracy governance and workflow processes, integrating the activities of the West Java Provincial DPRD leadership into social media represents a strategic step. This research aims to analyze how workflow processes and bureaucracy governance can be optimized through the use of social media to integrate the activities of the West Java Provincial DPRD leadership. The research method employed is descriptive analysis, collecting data from various relevant sources. Findings from this research indicate that the use of social media can enhance the effectiveness and responsiveness in bureaucratic workflow processes, as well as provide broader access to the public regarding information and activities conducted by the West Java Provincial DPRD leadership. The implications of this research provide a basis for the development of more efficient and targeted communication strategies in the context of bureaucracy governance in the West Java Provincial DPRD.